If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -2) = 42 Reorder the terms: 3(-2 + y) = 42 (-2 * 3 + y * 3) = 42 (-6 + 3y) = 42 Solving -6 + 3y = 42 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3y = 42 + 6 Combine like terms: -6 + 6 = 0 0 + 3y = 42 + 6 3y = 42 + 6 Combine like terms: 42 + 6 = 48 3y = 48 Divide each side by '3'. y = 16 Simplifying y = 16
| n+5-8=84 | | n+5-8=84 | | 5X-40+42+28X=-13 | | 26-m=-40 | | 8x(3x^2-2x+4)= | | 2y^2-12+5y=0 | | -3h+18h+-13h=20 | | -1x=18 | | T+15=-17 | | -12x+6x=18 | | -3n+11+7n=27 | | 0x+3=3x | | -11c+-8c+20c=7 | | x-3=3x+11 | | 0x+3=0x | | 250+20h=300 | | a=8+x | | 4x-7=6x-27 | | B^2-7b+5=0 | | x^2+4x-3= | | 0x+3=0 | | 2x+44=98 | | 7(T-2)+3T=5(2T+4)-10 | | -8-x=-15 | | 5x+6.5=8x-2.5 | | 20-10x= | | 8+10x=80 | | 3x-7(4+x)=-4(x+9) | | 8+10x=100 | | 3x(x-2)=x-9 | | 6x+4=90 | | x^2+11x-17=4x+1 |